2010
DOI: 10.1007/s10840-010-9478-4
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous right ventricular support during catheter ablation of intra-atrial reentrant tachycardia in an adult with a mustard baffle—A novel use of the Impella device

Abstract: Late sequelea following a Mustard operation for transposition of the great arteries (TGA) include atrial arrhythmias and dysfunction of the systemic right ventricle. Catheter mapping and ablation of atrial tachycardia in the setting of significant right ventricular dysfunction may result in hemodynamic compromise. We report the novel use of the Impella percutaneous microaxial flow pump to support cardiac output in an adult patient with a Mustard operation for TGA who experienced a cardiac arrest during a prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Similarly, electrophysiological activation and entrainment mapping and catheter ablation of nontolerated VT, particularly in patients with severe left ventricular dysfunction, are often not feasible without hemodynamic support. Several articles have already been published with case reports or small series of patients undergoing electrophysiological mapping and catheter ablation on circulatory support: the successful use of the Impella system was described by Fishberger et al 6 and Abuissa et al, 7 support with the TandemHeart system was reported by Friedman et al, 8 and the efficacy of ECMO was shown by Carbucicchio et al 9 and Thomas et al 14 The largest series during VT ablation has been with the use of the Impella 2.5 system (used with intravenous vasoactive agent support). 15 There is also an increasing number of reports describing the favorable effect of ECMO on survival with good neurological outcome in patients who underwent resuscitation, particularly for in-hospital cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, electrophysiological activation and entrainment mapping and catheter ablation of nontolerated VT, particularly in patients with severe left ventricular dysfunction, are often not feasible without hemodynamic support. Several articles have already been published with case reports or small series of patients undergoing electrophysiological mapping and catheter ablation on circulatory support: the successful use of the Impella system was described by Fishberger et al 6 and Abuissa et al, 7 support with the TandemHeart system was reported by Friedman et al, 8 and the efficacy of ECMO was shown by Carbucicchio et al 9 and Thomas et al 14 The largest series during VT ablation has been with the use of the Impella 2.5 system (used with intravenous vasoactive agent support). 15 There is also an increasing number of reports describing the favorable effect of ECMO on survival with good neurological outcome in patients who underwent resuscitation, particularly for in-hospital cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…a life-saving procedure during cardiopulmonary resuscitation or for hemodynamic support in high-risk coronary or electrophysiological interventions, [1][2][3][4][5] particularly in patients with severe left ventricle dysfunction undergoing electrophysiological mapping and tachycardia ablation. [6][7][8][9] To date, only small randomized trials comparing the safety and efficacy of these systems with intra-aortic balloon pump have been published [10][11][12] ; neither clinical nor experimental data on the direct comparison of these circulatory support systems are available. An estimation of the power of each support system is, however, essential for the selection of the most appropriate system for individual patients.…”
mentioning
confidence: 99%
“…Accordingly, in most reported cases, muscle resection has been performed before inflow cannula placement. [164][165][166] Future-generation devices, including catheter-based therapies 167 and smaller axial flow pumps, 168 may provide additional temporary and long-term support that may be more forgiving of size and orientation constraints. MCS for transposition of the great arteries has been reported with reasonable outcomes in small case series 164 ; however, apart from case reports, MCS for Fontan patients 169 has not been widely adopted.…”
Section: Mechanical Circulatory Supportmentioning
confidence: 99%
“…183 Despite the technical difficulties in implantation, an RV inflow cannula would appear to be superior because of the difficulty of atrial inflow in the setting of Mustard or Senning baffles where the narrow caliber of the atrial baffle could cause obstruction of the inflow cannula. Futuregeneration devices, including catheter-based therapies 184 and smaller axial flow pumps, [185][186][187] may provide additional temporary and long-term alternatives that may be more forgiving of the size and orientation constraints described.…”
Section: Surgical Therapy and Ventricular Assist Devicesmentioning
confidence: 99%